An integrated-empirical logistics perspective on supply chain innovation and firm performance - Mandal, Santanu; Korasiga, Venkateswar (Business: Theory and Practice, 2015)
Supply chains need to innovate constantly for maintaining their position in the marketplace and also to fight uncertainties. Hence firms are focusing on strategies for developing supply chain innovation. The current investigation adds to this emerging regime through investigating the influence of logistics capabilities viz. demand management capability, supply management capability, information management capability and coordination capability on supply chain innovation through logistics integration. Further, supply chain innovation helps a firm to sustain its position in the market place through generation and launching of new products and services. Accordingly, the influence of supply chain innovation on firm performance is also investigated. Data is collected from logistics, purchasing and supply chain professionals working in different industries in India. The findings based on 169 responses largely support our proposed relationships.